Online videos: The hidden curriculum. (11th February 2022) - Dias da Silva, Marco Antonio; Pereira, Andresa Costa; Vital, Sibylle; Mariño, Rodrigo; Ghanim, Aghareed; Skelton‐Macedo, Mary Caroline; Kavadella, Argyro; Kakaboura, Afrodite; Uribe, Sergio E.; Johnson, Ilona; Dalessandri, Domenico; Walmsley, Anthony Damien
Abstract: Introduction: Dental undergraduates will access the Internet searching for learning materials to complement their training; however, open access content is not generally recommended by dental schools. This study aimed to evaluate how dental students are using online video content. Materials and Methods: Students from eight Universities (Athens, Birmingham, Brescia, Cardiff, Melbourne, Paris, Sao Paulo and Valdivia) representing three continents were invited to complete a survey on their access and learning from online videos. Results: International students behave similarly when studying dental content online. Of 515 respondents, 94.6% use the Internet as a learning tool. It was observed that videos are not frequently recommended during didactic lectures (9.6%). But many students (79.9%) will use YouTube for their learning which includes clinical procedures. Students will check online content before performing procedures for the first time (74.8%), to understand what was explained in class (65.9%) or read in books (59.5%), to relearn clinical techniques (64.7%) and to visualise rare procedures (49.8%). More than half of the students do not fully trust the accuracy or the reliability of online content. This does not prevent students from watching and sharing dental videos with classmates (64.4%). The content watched is not shared with teachers (23.3%) even when it contradicts what was learnt in the school (38.2%). Conclusion: This study concludes that students regularly integrate open access digital resources into learning portfolios but are hesitant to inform their teachers about their viewing habits. Students wish to receive critical skills on how to evaluate the material they encounter outside their traditional learning space.